Utilizing Lactipro (Megasphaera elsdenii NCIMB 41125) to accelerate adaptation of cattle to high-concentrate diets and improve the health of high-risk calves - Miller, Kevin Alan (Kansas State University, 2013)
Four experiments were conducted to evaluate the potential for accelerating adaption to high-concentrate diets and improving the health of high-risk calves, by administering an oral dose of Megasphaera elsdenii. Lactipro, a probiotic containing a live culture of Megasphaera elsdenii (10[superscript]9 CFU/mL), was orally dosed to cattle (100 mL) at initial processing. In experiment 1, heifers were adapted to a high-concentrate diet in 21 d without Lactipro or dosed with Lactipro and adapted in 16 d, 11 d, 6 d, or fed the high-concentrate diet d 1. Accelerating adaptation decreased DMI (P = 0.09), ADG, and efficiency (P < 0.05) during the first 30 d compared to cattle adapted over 21 d. Over 129 d, DMI and ADG were not different (P ≥ 0.12), but efficiency tended (P = 0.08) to be better for cattle adapted over 21 d. Liver abscesses and carcass traits were not different between treatments, with the exceptions of LM area (quadratic, P < 0.01) and marbling (linear, P = 0.07), which tended to increase with accelerated adaptation protocols. In experiment 2, cattle dosed with Lactipro and placed directly onto the finishing diet required less roughage (P < 0.01), tended to have lower DMI (P = 0.07), better quality grade (P ≤ 0.07), and similar ADG and efficiency (P ≥ 0.14) compared to cattle adapted over 18 d without Lactipro. Over the first 24 d DMI, DM fecal output, and apparent total tract NDF digestibility were greater (P < 0.01) for cattle adapted over 18 d. In Experiment 3, dosing calves, of Mexican origin, with Lactipro did not affect performance (P ≥ 0.16). Second antibiotic therapies for undifferentiated bovine respiratory disease (UBRD) tended (P = 0.06) to be lower in calves dosed Lactipro. In Experiment 4, dosing calves from Texas with Lactipro increased DMI, ADG, and efficiency (P ≤ 0.05). The incidence of 1st and 2nd antibiotic therapies for UBRD (P < 0.01) and medical cost were decreased for calves dosed Lactipro (P < 0.05). Dosing cattle with Lactipro allows for accelerated adaption to high-concentrate diets, decreases reliance on roughages, and improves health during the receiving period.
Keywords: Megasphaera elsdenii; Lactipro; Diet adaptation; Roughage; Bovine respiratory disease; Animal Sciences (0475)